2021
DOI: 10.1080/23748834.2021.1894843
|View full text |Cite
|
Sign up to set email alerts
|

The urban syndemic of COVID-19: insights, reflections and implications

Abstract: This editorial introduces the origin, purpose and scope of a Special Issue on COVID-19. It brings together 43 contributions from across the globe that examine the way in which COVID-19 has challenged the way we think about urban design, spatial planning and city governance. The editorial draws out a number of key messages from this body of work, highlighting how the impact of COVID-19 has been most devastating when combined with the existing vulnerabilities and chronic ill-health experienced in pre-pandemic ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…However, much subsequent research, including a special issue of Urban Studies ( Duminy, 2021 ; Kawlra and Sakamoto, 2021 ; McFarlane, 2021 ; Preece et al, 2021 ), has shown that inequality was a major factor in spreading the pandemic. Thus, the COVID-19 epidemic has been labelled a ‘syndemic’, due to the disease’s devastating impact on pre-existing health and socio-economic vulnerabilities in urban spaces ( Ellis et al, 2021 ).…”
Section: On Disease Fears Segregation and The Long Persistence Of Ter...mentioning
confidence: 99%
“…However, much subsequent research, including a special issue of Urban Studies ( Duminy, 2021 ; Kawlra and Sakamoto, 2021 ; McFarlane, 2021 ; Preece et al, 2021 ), has shown that inequality was a major factor in spreading the pandemic. Thus, the COVID-19 epidemic has been labelled a ‘syndemic’, due to the disease’s devastating impact on pre-existing health and socio-economic vulnerabilities in urban spaces ( Ellis et al, 2021 ).…”
Section: On Disease Fears Segregation and The Long Persistence Of Ter...mentioning
confidence: 99%
“…The next steps for urban and territorial planning for health must be anchored in a shared vision for a healthier future and the urgency of action, considering the risks to urban health uncovered by the COVID-19 crisis (Ellis et al, 2021 ). WHO’s ‘Manifesto for a healthy and green COVID-19 recovery’ (WHO, 2020a ) places urban and territorial planning at the core of the action needed to revert the ‘escalating damage to the ecological systems that sustain all human health and livelihoods’, including prescriptions directly related to urban and territorial planning.…”
Section: What Have We Learnt?mentioning
confidence: 99%
“…To deepen our understanding of COVID-19 in terms of urban governance, form and design, during the early sages of the pandemic in 2020 the journal solicited an international set of papers. These have been curated into a set of 51 think pieces as 'The COVID-19 Lockdown Papers' and published in a special issue 'Cities, health and COVID-19: Initial reflections and future challenges' (Ellis et al 2021).…”
Section: Covid-19 and Implicationsmentioning
confidence: 99%